Potencializando o interesse dos novos alunos, nativos digitais, nos cursos de engenharia de computação e afins, através de um processo ativo de evolução das habilidades e competências já existentes em vez de um processo de reconstrução - Ferreira, Divino Rosa da Silva (2016)
The difference between what is desired and what is to join an engineering course makes new students have an early demotivation with the course. This paper presents a methodology that keeps the student in your digital world not away from your mobile device (cell phone), but making it a tool for learning. Through hands-on lab the student is replaced since the beginning of the course the real result of what you and taught. Thus the student keeps the stimulus and interest in each new experience presented during the course. At the end of the period the student is already able to develop useful projects of residential and / or commercial application. What is expected of a student of engineering is that it is the end of the course an engineer. The proposed work is to engineer it from your ticket.